1987
DOI: 10.1038/ki.1987.119
|View full text |Cite
|
Sign up to set email alerts
|

Anti-α-galactosyl antibodies and immune complexes in children with Henoch–Schönlein purpura or IgA nephropathy

Abstract: Episodes of hematuria in IgA nephropathy or Henoch-Schönlein purpura are frequently associated with microbial infections. Some of those infectious agents bear alpha-galactosyl residues on their cell surface. These observations prompted us to determine, by passive hemagglutination, the titers of natural anti-galactosyl antibodies in the serum of children presenting with Henoch-Schönlein purpura (10 cases) or IgA nephropathy (7 cases). Antibody titers of normal subjects (103 cases), children with a pharyngitis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…Binding of anti-Gal IgA to the pili of Neisseria meningitidis has been shown to compete with anti-Gal IgG binding and to inhibit complementmediated cytolysis of piliated strains (12). Infection with E. coli and other gram-negative bacteria has been associated with elevated anti-Gal antibodies and autoimmune disease due to IgA immune complex deposition in children with HenochSchönlein purpura or IgA nephropathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of anti-Gal IgA to the pili of Neisseria meningitidis has been shown to compete with anti-Gal IgG binding and to inhibit complementmediated cytolysis of piliated strains (12). Infection with E. coli and other gram-negative bacteria has been associated with elevated anti-Gal antibodies and autoimmune disease due to IgA immune complex deposition in children with HenochSchönlein purpura or IgA nephropathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Gal is an IgG antibody (Ab) that is present in large amounts in normal subjects and patients with malignancies, comprising ∼1% of serum-circulating IgG (16)(17)(18). Anti-Gal Ab specifically interacts with α-gal epitopes on cell surface glycolipids and glycoproteins, and it is produced throughout life due to antigenic stimulation by bacteria of the gastrointestinal flora (19).…”
Section: Introductionmentioning
confidence: 99%
“…Since Towbin et al [14] previously reported that the circulating antibody to mouse laminin in Chagas' disease, American cutaneous leishmania sis and normal individuals recognizes terminal galactosyl-a il ->3)-galactose epitopes and since Davin et al [15] reported earlier the presence of anti-a-galactosyl antibody in sera from IgA neph ropathy patients, the possibility exists that the IgA antimouse lam inin antibody we detected might recognize the same epitopes as anti-a-galactosyl antibody. To elucidate this possibility, inhibition ELISA using melibiose (which contains an a-galactosyl residue) and treatment of the solid-phase mouse laminin by a-galactosidase were studied.…”
Section: Antilaminin and Fibronectin Elisa Assaymentioning
confidence: 96%